The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1104/pp.85.2.502
|View full text |Cite
|
Sign up to set email alerts
|

Polygalacturonase Gene Expression in Rutgers, rin, nor, and Nr Tomato Fruits

Abstract: ABSTRACrPolygacturonse (PG) The ripening of tomato fruit is characterized by a series of coordinated biochemical and physiological changes which collectively contribute to the final texture, color, and flavor ofthe ripe fruit. The softening of tomato fruit during ripening has been studied extensively during the past 20 years and a large body of evidence has accumulated which suggests the cell wall enzyme PG2 plays a major role in this process. Several lines of evidence which support this include: (a) a rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
1
3

Year Published

1990
1990
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 19 publications
8
71
1
3
Order By: Relevance
“…The results are similar to the findings of scientists who worked on the role of PG during fruit development in various kinds of fruits and found a correlation, as PG activity and softening occurs simultaneously in cherry (Barrett and Gonzalez, 1994), date (Hasegawa et al, 1969), durian (Ketsa and Daengkanit, 1999), kiwifruit (Wang et al, 2000), mango (Ketsa et al, 1998), papaya (Paull and Chen, 1983), pear (Ahmed and Labavitch, 1980), pepper (Rao and Paran, 2003;Arancibia and Motsenbocker, 2006), tobacco (Osteryoung et al, 1990), and tomato (Hobson, 1965;Crookes and Grierson, 1983;Huber, 1983;DellaPenna et al, 1987;Bird et al, 1988;Biggs and Handa, 1989;Smith et al, 1990;Fenwick et al, 1996).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The results are similar to the findings of scientists who worked on the role of PG during fruit development in various kinds of fruits and found a correlation, as PG activity and softening occurs simultaneously in cherry (Barrett and Gonzalez, 1994), date (Hasegawa et al, 1969), durian (Ketsa and Daengkanit, 1999), kiwifruit (Wang et al, 2000), mango (Ketsa et al, 1998), papaya (Paull and Chen, 1983), pear (Ahmed and Labavitch, 1980), pepper (Rao and Paran, 2003;Arancibia and Motsenbocker, 2006), tobacco (Osteryoung et al, 1990), and tomato (Hobson, 1965;Crookes and Grierson, 1983;Huber, 1983;DellaPenna et al, 1987;Bird et al, 1988;Biggs and Handa, 1989;Smith et al, 1990;Fenwick et al, 1996).…”
Section: Discussionsupporting
confidence: 78%
“…The deduced amino acid sequence of CaPG showed most similarity to active endo-PG enzyme isolated by Chen et al (2010). There was little expression of CaPG in the green stage of both cultivars, as also found by DellaPenna et al (1987); Daengkanit, (1999), andWang et al (2000) reported that PG is not expressed at early stages of fruit maturity. CaPG expression was quite weak during the breaker stage in cv.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Protein was extracted from tobacco tissue essentially as previously described for tomato fruit tissue (DellaPenna et al, 1987). Briefly, leaf tissue was homogenized on ice in 1 volume to 3 volumes of 20 mM Tris, 5 mM 2-mercaptoethanol, pH 7, or 20 mM Mes, 3 mM DTT, pH 5.5 (low-salt buffers).…”
Section: Protein Extraction and Polygalacturonase Assaysmentioning
confidence: 99%